The Possibilities of Implementing the „European Green Deal” Strategy in Poland as an Opportunity to Restructure the Area of Green Logistics - Bogucka Anna; Lis Karolina (2022)
The subject of the article is implementation Strategy of Green Deal in Poland such as a next step of reduction of pollution in European Union. Membership in the European Union brings challenges, which Poland, as a member must realized. Modern industrialization causes complication , with ecologically aware countries must cope with. Caring for the environment is becoming synonymous with conscious humanity.There was a need to create a strategy that will set the goal of upgrading technology to achieve zero emissions by 2050. The implementation of the Green Deal strategy comes with legal constraints that should guide every member of the European Union community. The research objective of the article is determining the role of the implementation of the newly adopted Green Deal strategy in the European Union. The research hypothesis of the article is that the European Union as a united community of states strives to unify the level of pollution emission reduction and the Green Deal strategy combines legal conditions of coexistence of the states in Europe. The authors applied research methods in the form of desk research (analysis of existing data), analysis of individual cases, analysis of legal documents and analysis of scientific literature. The reseaarch concluded that the implementation of the New Green Deal by the member states is a necessary step to reduce emissions of pollutants as a plan of action of countries until 2050.